Analisis Peran Himpunan Mahasiswa Program Studi Pendidikan Bahasa Arab Dalam Membentuk Lingkungan Bahasa Arab (Bi’ah Lughawiyyah) Di Program Studi Pendidikan Bahasa Arab Universitas Islam Negeri Datokarama Palu - Ahmad Asse; Titin Fatimah; Putri Ayu Diah Agustina (Program Studi Pendidikan Bahasa Arab (PBA), Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Instutut Agama Islam Negeri (IAIN) Palu, 2022)
This research is a qualitative descriptive study. The purpose of this study is to describe the role of HMPS PBA in shaping the Arabic language environment (Bi'ah lughawiyyah). Data collection techniques include observation, interviews and documentation. While the data analysis techniques used are data reduction, data presentation and conclusion drawing, and also checking the validity of the data. Sources of data obtained from primary and secondary data found in research locations that are relevant to the problem under study. The results of the study indicate that the role of the student association of the Arabic language education study program in shaping the Arabic language environment (bi'ah lughawiyyah) is to carry out work programs that can support the formation of the Arabic language environment (bi'ah lughawiyyah). The work programs that can support the formation of the Arabic language environment (bi'ah lughawiyyah), namely; Hearing Aspirations, Daily vocabulary, Halaqah Arabiyyah, speech training, and Arts (Poetry, singing Arabic and Jepeng).